PERBEDAAN TINGKAT DEPRESI ANTARA IBU YANG MEMPUNYAI ANAK MENTAL RETARDATION (MR) DENGAN IBU YANG MEMPUNYAI ANAK ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) DI SLB SE KOTA BATAM - Rini Susanti; Rusdani (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
The first response from parents tends to reject / denial. For mothers who cannot accept reality, they tend to experience depression. This study aims to analyze whether there are differences in the level of depression between mothers who have Mental Retardation (MR) children and mothers who have children with Attention Deficit Hyperactivity Disorder (ADHD) in Batam City SLB in 2018. The method of this study was observational analytic, with a cross sectional study approach conducted at the SLB in Batam City from October to December 2018. The sampling technique was total sampling with a total sample of 70 mothers. Univariate analysis is presented in the frequency distribution table and bivariate analysis using Mann Whitney. The results of the study showed that the depression rate of mothers who had MR children in SLB in Batam in 2018 had 14 respondents (40%) mild depression, 21 respondents (60%) moderate depression, and 0 respondents (5.7%) depressed. weight, while the depression level of mothers who have ADHD children is 16 respondents (45.7%) mild depression, 19 respondents (54.3%) moderate depression, and 0 respondents (0%) major depression. The Mann Whitney analysis results obtained p = 0.026 where p is smaller than the significant level that is (α) = 0.05.Based on this study it was concluded that there were differences in the level of depression between mothers who had Mental Retardation (MR) children and mothers who had children with Attention Deficit Hyperactivity Disorder (ADHD) in Batam City SLB in 2018.